Ankaferd hemostat (ABS) as a potential mucosal topical agent for the management of COVID-19 syndrome based on its PAR-1 inhibitory effect and oestrogen content. (October 2020) - Beyazit, Fatma; Beyazit, Yavuz; Tanoglu, Alpaslan; Haznedaroglu, Ibrahim C.
Abstract: COVID-19 due to the SARS-CoV-2 infection is a multi-systemic immune syndrome affecting mainly the lungs, oropharyngeal region, and other vascular endothelial beds. There are tremendous ongoing efforts for the aim of developing drugs against the COVID-19 syndrome-associated inflammation. However, currently no specific medicine is present for the absolute pharmacological cure of COVID-19 mucositis. The re-purposing/re-positioning of already existing drugs is a very important strategy for the management of ongoing pandemy since the development of a new drug needs decades. Apart from altering angiotensin signaling pathways, novel drug candidates for re-purposing comprise medications shall target COVID-19 pathobiology, including pharmaceutical formulations that antagonize proteinase-activated receptors (PARs), mainly PAR-1. Activation of the PAR-1, mediators and hormones impact on the hemostasis, endothelial activation, alveolar epithelial cells and mucosal inflammatory responses which are the essentials of the COVID-19 pathophysiology. In this context, Ankaferd hemostat (Ankaferd Blood Stopper, ABS) which is an already approved hemostatic agent affecting via vital erythroid aggregation and fibrinogen gamma could be a potential topical remedy for the mucosal management of COVID-19. ABS is a clinically safe and effective topical hemostatic agent of plant origin capable of exerting pleiotropic effects on the endothelial cells, angiogenesis, cell proliferation and vascular dynamics. ABS had been approved as a topically applied hemostatic agent for the management of post-surgical/dental bleedings and healing of infected inflammatory mucosal wounds. The anti-inflammatory and proteinase-activated receptor axis properties of ABS with a considerable amount of oestrogenic hormone presence highlight this unique topical hemostatic drug regarding the clinical re-positioning for COVID-19-associated mucositis. Topical ABS as a biological response modifier may lessen SARS-CoV-2 associated microthrombosis, endothelial dysfunction, oropharyngeal inflammation and mucosal lung damage. Moreover, PAR-1 inhibition ability of ABS might be helpful for reducing the initial virus propagation and mocasal spread of COVID-19.